Aspects of adhesion tests on resin–glass ceramic bonding. Issue 9 (September 2017) - Wong, Andrew Chi Ho; Tian, Tian; Tsoi, James Kit Hon; Burrow, Michael Francis; Matinlinna, Jukka Pekka
Abstract: Objectives: This study aimed to compare and contrast two resin–ceramic bond strength tests, the tensile bond strength and the four-point bending tests. The effects of hydrofluoric acid (HF) etching time and storage condition on bond strength were also studied. Methods: Ceramic beams (N = 480) with the dimensions of 2.00 × 2.00 × 12.45 mm 3 were sectioned from lithium disilicate ceramic ingots (IPS e.max CAD), then polished and fired for final crystallization. The joint surfaces were etched with HF gel (IPS Ceramic etching gel) for 20 s, 40 s, or 60 s of each group (n = 160). Then, a silane coupling agent (Vitasil ® ) was applied in a single application on the HF etched surfaces, left for 60 s before air-drying. Two beams were bonded together with resin composite cement (Variolink II ® ) in a tailored-mold (2.00 × 2.00 × 25.00 mm 3 ) to control cement thickness to 0.10 mm and then light cured on both sides. The bonded specimens were further divided into two groups (n = 40): (1) tested one day after luting (dry); and (2) tested after storage in 37° C distilled water for 4 weeks. Two mechanical tests were used (n = 20): the tensile bond strength and four-point bending tests. Bond strength results were subjected to two-way AoV, and Weibull statistics with α = 0.05. Fracture surfaces were examined visually and verified using light microscopy. Results: The four-point bending test showed a higher consistency than the tensile bond strength test using Weibull statistics ( p < 0.01). The effect of HF etching time on the flexural strength was significant, with longer HF etching times decreasing the flexural strength ( p < 0.01). Storage also had a significant effect on the flexural strength ( p < 0.01). However, HF etching time did not have a significant effect on the tensile bond strengths ( p > 0.05) and the influence of the storage time was marginally significant ( p < 0.05). More than 75% of specimens failed adhesively in the four-point bend test while a mixture of adhesive, cohesive and mixed failures was observed in the tensile bond test. Significance: The four-point bending test might be a better approach to evaluate bond strengths. Increased HF etching time and a longer storage period resulted in a decrease in the flexural bond strength. However, both HF etching time and storage time had no significant effect on the tensile bond strengths.